Reduction method with simulated annealing for semi-infinite programming - Pereira, Ana I. (2011)
Semi-infinite programming (SIP) problems are characterized by a finite number of variables and an infinite number of constraints. The class of the reduction methods is based on the idea that, under certain conditions, it is possible to replace the infinite constraints by a finite set of constraints, that are locally sufficient to define the feasible region of the SIP problem. We propose a new reduction method based on a simulated annealing algorithm for multi-local optimization and the penalty method for solving the finite problem.